Neural correlates of the attention training technique as used in metacognitive therapy – A randomized sham-controlled fMRI study in healthy volunteers - Jahn, Niklas; Sinke, Christopher; Kayali, Özlem; Krug, Svenja; Leichter, Erik; Peschel, Stephanie; Müller, Torben; Burak, Alev; Krüger, Tillmann H. C.; Kahl, Kai G.; Heitland, Ivo (Frontiers in Psychology, 2023)
The Attention Training Technique (ATT) as part of metacognitive therapy is a psychotherapeutic treatment method used to enhance top-down attentional flexibility and control. This study investigated potential neurocognitive changes due to ATT and its underlying neural mechanisms using pre-to-post functional magnetic resonance imaging (fMRI). 54 healthy participants were subjected to a randomized, sham-controlled attention training and evaluated using a neurocognitive test battery that partly took place in an fMRI environment. Participants received two doses ATT or sham ATT daily for one week. On day eight, all subjects completed the neurocognitive test battery again. After the training, the ATT group showed a significant improvement in reaction times regarding attentional disengagement compared to the sham ATT group. fMRI data showed decreased levels of activation in the anterior cingulate cortex (ACC) when comparing the ATT group to the sham ATT group during attentional disengagement post intervention. No ATT > sham ATT effects were found regarding selective auditory attention, working memory performance and inhibitory control. These findings putatively indicate that ATT facilitates faster attention allocation and increased attentional flexibility in healthy subjects. The fMRI results suggest this ATT-dependent improvement is accompanied by reduced ACC activity, indicating a more flexible attentional state.